Supramolecular DNA Three-Way Junction Motifs With a Bridging Metal Center - Takezawa, Yusuke; Shionoya, Mitsuhiko (Frontiers in Chemistry, 2020)
Various nano-sized supramolecular architectures have been constructed from DNA molecules via sequence-dependent self-assembly. A DNA three-way junction (3WJ), consisting of three oligonucleotides that are partially complementary to each other, is one of the simplest DNA supramolecular structures. This minireview covers studies on DNA 3WJ motifs bridged by an interstrand metal complex with some related works. The incorporation of interstrand metal complexes into DNA has attracted increasing attention because it potentially allows for metal-dependent regulation of the thermal stability and the structure of DNA supramolecules. Metal-bridged DNA 3WJs were synthesized from three DNA strands containing a bipyridine (bpy)-modified nucleotide in the presence of appropriate metal ions. The bpy-modified DNA strands were crosslinked by an interstrand 3:1 metal complex (NiII(bpy)3 etc.) at the junction core. As a result, the thermal stability of the 3WJs was significantly enhanced upon metal complexation. Furthermore, metal-mediated structural transformation between DNA duplexes and 3WJs was demonstrated by using the same bpy-modified DNA strands. A mixture of bpy-modified strands and their natural complementary strands were self-assembled exclusively into duplexes in the absence of any transition metal ions. In contrast, addition of NiII ions induced the formation of 3WJs through the formation of an interstrand NiII(bpy)3 complex, which served as a template for the 3WJ assembly. Because DNA 3WJ structures are essential structural motifs for DNA-based nanoarchitectures, the metal-mediated stabilization and structural induction of metal-locked 3WJs would lead to many potential applications to artificial DNA architectures.